Relationships between emotional intelligence, mental resilience, and adjustment disorder in novice nurses: a cross-sectional study in China - Peng, Man; Xu, Meijuan; Yang, Hui; Zhang, Qiuxuan; Lai, Lijun; Liu, Yanmei; Xie, Qimei; Ma, Xuexia; Mao, Xiaoqun (Frontiers in Public Health, 2025)
ObjectiveThis study aims to explore the relationship among adjustment disorder, emotional intelligence, and mental resilience in newly licensed registered nurses.MethodThis study adopts a cross-sectional design to explore the factors influencing work adaptation and mental resilience among newly graduated nurses with <3 years of clinical experience. The research was conducted by distributing a comprehensive, multi-part questionnaire to a targeted sample of new nurses across various healthcare settings. The questionnaire was meticulously designed to capture a holistic view of the participants' personal, professional, and psychological profiles, which included the Personal and Professional Characteristics Questionnaire, the Work Adaptation Difficulties Scale, the Mental Resilience Scale, and the 10-item Connor-Davidson Resilience Scale.ResultsA total of 445 new nurses completed the questionnaire. The mean age of participants was 24.50 ± 2.77 years. Adjustment disorder negatively affected mental resilience (r = −0.460**, P < 0.001) and emotional intelligence (EI) (r = −0.380**, P < 0.001). Conversely, mental resilience positively influenced emotional intelligence (r = 0.714**, P < 0.001). The emotional perception (EP) dimension was negatively correlated with adjustment disorder (r = −0.396**, P < 0.001) but positively associated with increased mental resilience (r = 0.702**, P < 0.001).ConclusionFindings suggest that higher levels of emotional intelligence and psychological resilience contribute significantly to enhanced work adaptation and the mitigation of psychological stress among nurses. Furthermore, job satisfaction appears to be a key predictor in the onset of adjustment disorders. These results underscore the necessity for head nurses and hospital administrators to adopt proactive measures aimed at promoting the psychological well-being of nursing professionals. Targeted interventions that foster emotional resilience and job satisfaction may serve as effective strategies to prevent maladaptive adjustment outcomes in high-stress clinical environments.